Climate Change Mitigation and Adaptation Strategies Used by Farmers in Imo State Nigeria - J. P. Okoroh; M. O. Olaolu; E. M. Igbokwe (Journal of Agricultural Extension, 2016)
This study examined the strategies employed by farmers to mitigate the effects of climate change on agricultural practices. A structured interview schedule was used to collect data from 220 farmers. Frequency, percentages and mean statistic were used to present the results of the data collected. The results show that the mean age of the farmers was 51 years with an average of 22 years of farming experience. The majority (75%) of the farmers were aware of climate change within their environment. Self-observation and experience (42.4%) over the years was the source of awareness of climate change. The majority (73.6%) of the farmers opined that in recent times, flooding had increased which is an indication of climate change. Reduction in the use of generator to get power in the farmers’ houses (69.1%) and crop rotation practices (67.3%) were mitigation and adaptation strategies employed by the farmers against the effect of climate change. The study recommends that government of states should enforce the policy on afforestation as a mitigation measure against climate change.